USA. Collapse or extinguishment? Scenarios - V. V. Shumov (Informaciâ i Innovacii)
We are witnessing a geopolitical inversion - the change of the world leader. Similar phenomena have already occurred in world history, therefore, it seems important to carry out a scientific analysis of both the processes of geopolitical inversion and deeper processes associated with the sustainable and successful development of states, the coalitions and international institutions they create. The analysis of objective trends was carried out using a mathematical safety model; a scenario approach was applied to take into account subjective and poorly predictable factors.